Ocean literacy in managing marine protected areas: bridging natural and cultural heritage - Gómez, Sílvia; Garriga, Anna; Bosch, Maria Teresa; Bosch, Marta; Villasante, Sebastian; Salazar, Janire (Frontiers in Marine Science, 2025)
This study explores the factors driving the integration of ocean literacy into the management of Marine Protected Areas, highlighting its role as a powerful tool to transform the human–ocean relationship to improve conservation efforts. A survey was completed by 197 visitors in Cap de Creus (Northeastern Catalonia, Spain). The findings show that visitors who were more willing to pay for conservation valued cultural and natural heritage more highly, and held more positive opinions about protection, regardless of their knowledge and despite their lower income and educational level. These results show us that knowledge does not necessarily indicate greater environmental awareness. The need to consider the marine environment as a cultural-natural embedded heritage is highlighted to foster a cultural connection, inspire commitment to its protection and promote conservation that ensures human well-being and health. Finally, some recommendations are offered to improve the integration of OL in MPA policies.